Ethnotherapeutic Uses and Phytochemical Composition of Physalis peruviana L.: An Overview - Kasali, F´elicien M.; Tusiimire, Jonans; Kadima, Justin N.; Tolo, Casim U.; Weisheit, Anke; Agaba, Amon G. (The Scientific World Journal, 2021)
Background. Plant-derived medicines are widespread and continue to increase in traditional and modern medicine, especially in developing countries. Physalis peruviana L. is among the most used plants in conventional medication worldwide. +is review aimed to highlight the ethnotherapeutic uses and phytochemical status of identified compounds in P. peruviana. Methods. Data were collected from Google Scholar, PubMed/Medline, SciFinder, Science Direct, Scopus, the Wiley Online Library, Web of Science, and any other helpful search engine using Physalis peruviana as the primary keyword. Results. Some countries, worldwide, use P. peruviana in their traditional medicine system to manage diverse ailments, mainly diseases and gastrointestinal tract disorders (25.33%). Leaf was the mostly used part (49.28%), prepared by decoction (31.58%) and overall administrated orally (53.57%) as the main route of admission. Around 502 phytoconstituents were identified in different plant parts, especially fruit (38.19%) ethanol/ethyl acetate extract. In most cases (36.17%), the solvent of the extract was not specified. Several phytochemical classes were found in the plant, especially terpenes (26.09%) and phenolic compounds (14.94%). Esters were also abundant (11.55%). In the terpenes category, carotenoids were the most abundant (11.15% followed by monoterpenes (8.76%) and diterpenes (3.18%). However, flavonoids (5.17%) followed by cinnamic acid derivatives (3.99%), monophenolic compounds (1.79%), and phenolic acids (1.33M) are the most reported phenolic compounds. Hexadecanoic acid (palmitic acid) was the most cited (five times). Conclusion. P. peruviana plays an essential role in managing diseases in some countries and is rich in chemical compounds, which need to be isolated and investigated pharmacologically before clinical trials
Keywords: Phytochemical Composition; Physalis peruviana; traditional and modern medicine